2020
DOI: 10.1155/2020/8895913
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Mechanical Characterization of Raffia vinifera Pith

Abstract: In this paper, the physicochemical and mechanical properties of Raffia vinifera pith (RVP) are discussed. Microscopic observations have shown that the structure of the RVP is similar to that of a composite consisting of natural fibers. The effective area ratio of Raffia vinifera (RV) fibers was evaluated along the raffia stem using ImageJ software, and it decreases from the periphery to the center. Energy dispersion spectrometer (EDS) analysis shows that RVP is essentially composed of carbon and oxygen. Densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Palm has been proven to have minerals like calcium [ 11 ]. The Raphia vinifera fruit pulp and pericarps were found to contain a high concentration of saponins, alkaloids, and oxalate; a moderate concentration of tannin, flavonoid, and steroid; and a low concentration of phytate, phenol, and glycoside, which are responsible for its therapeutic activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palm has been proven to have minerals like calcium [ 11 ]. The Raphia vinifera fruit pulp and pericarps were found to contain a high concentration of saponins, alkaloids, and oxalate; a moderate concentration of tannin, flavonoid, and steroid; and a low concentration of phytate, phenol, and glycoside, which are responsible for its therapeutic activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research on toxicological effects of medicinal plants and their extract is crucial in the development of drugs and to rise human safety [ 17 ]. Many toxicological studies have been carried out using Raphia vinifera on fish [ 11 ], but studies hardly describe the biochemical toxicity of this plant on rats. This investigation was therefore carried out to evaluate antiproliferative potential of Raphia vinifera extract and its constituents, as well as the toxicity of the crude extract.…”
Section: Introductionmentioning
confidence: 99%
“…ey have a length of 5 to 10 m and a diameter between 2 and 10 cm [2,3]. Cork consists of about 35.8% to 54.5% fibers [4] aligned lengthwise in a natural matrix. e mechanical properties of this natural matrix were determined by [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cork consists of about 35.8% to 54.5% fibers [4] aligned lengthwise in a natural matrix. e mechanical properties of this natural matrix were determined by [4]. Studies on the anatomy and physical properties of raffia vinifera bamboo have shown that the physical properties of this material approach those of lightweight wood [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation